Gambaran Peresepan Antibiotik terhadap Pengobatan Pasien ISPA di Klinik Utama Pupuk Kujang Cikampek - Ayunda Shita Devi; Rida Emelia (Syntax Corporation Indonesia, 2021)
ISPA treatment is an acute infection that attacks one or more parts of the airways from the nose to the alveoli, including the adnexan, namely the sinus, middle ear cavity and pleura. Basically, the principle of rational use of antibiotics is the selection of antibiotics that are selective against infecting microorganisms and effectively destroying infecting microorganisms. The method in this study was descriptive survey, which describes antibiotic prescribing of ARI treatment based on type of antibiotic and amount of drug in clinic Kujang,Cikampek. Based on the data obtained, the overall results of antibiotics prescribing in Januari – Maret 2021 at Clinic Kujang Cikampek were 719 Prescription and antibiotics prescribing for ARI were 250 Prescription (34.77%). The results of this study can be concluded that the number of antibiotics that were most prescribed in January were Zibramax 500mg as many as 29 prescriptions (39,19%); in February the most prescribed antibiotics were Zibramax 500mg with 26 prescriptions (47.27%); in March the most prescribed antibiotic was Zibramax 500mg with 55 prescriptions (45.45%)